Effect of MoSi2 on the wettability of SiCp/MoSi2(p) substrates for prospective Al-based composites via pressureless infiltration - J. Tapia-López; M.I. Pech-Canul; H.M. Hdz-García; J.L. Rodríguez-Galicia; R. Muñoz-Arroyo (Journal of Materials Research and Technology)
The quantitative influence of using recycled and reagent-grade MoSi2 particle (MoSi2(p)) powders, as well as evaluating the effect of % MoSi2(p) powders and SiC particles (SiCp) in compact substrates, % porosity, temperature, and dwell time on the wettability of SiCp/MoSi2(p) compacts by an Al–Mg–Si alloy were investigated. Evaluating and comparing reagent-grade or recycled MoSi2 is essential because the low-cost recycled material may convey phases that influence the wettability, and reagent-grade MoSi2 may impose affordability issues. The optimum wettability conditions were determined, and the contact angle (θ) and liquid‒vapor surface tension (γl-v) were projected and experimentally verified. From ANOVA, the parameters most significantly impacting (θ) and (γl-v) are the MoSi2(p) content and type. For contact angle, the corresponding contributions are 47% and 31%, while for surface tension, they are 32% and 18%, respectively. Under optimal conditions, equilibrium θ and γl-v values as low as 43° ± 6° and 234 ± 20 mN/m are obtained, which are favorable compared with the values predicted for 50% porosity. A comparison of the four different substrates revealed the beneficial effect of adding reagent-grade MoSi2(p) powders on the SiCp compacts, manifested by a 52% decrease in θ. The results are promising for developing Al/SiCp/MoSi2(p) composites by non-assisted or pressureless infiltration.